EVALUASI KINERJA ANGKUTAN PENUMPANG SPEED BOAT RUTE TARAKAN-TANJUNG SELOR - Sabir, Sabir; Syarif, Iif Ahmad (Civil Engineering Scientific Journal, 2023)
ABSTRACT: The condition of operators at Tengkayu I Port in North Kalimantan is often seen carrying passengers exceeding the Speed Boat's loading capacity in order to gain more profits without thinking about passengers comfort and safety. Thus, the passengers' comfort and safety were neglected. The Customer Satisfaction Index (CSI) method is a measurement form used to calculate the satisfaction level of all service attributes by paying more attention to the calculated expectation level. The Importance Performance Analysis (IPA) method was used to analyze or compare the service quality perceived by the service users based on the expected satisfaction level. Research conducted using the CSI method can be concluded that the overall service attributes on the Speed Boat transportation service on the Tarakan Tanjung Selor route are good. The service attribute in the terminal has an index number of 65.72%, while the service attribute on the ship itself has an index number of 67.60%. The passengers' satisfaction level to the facilities provided at port Tengkayu I using the IPA method was classified into 4 quadrants. The facilities provided at the port station had 5 (five) service facilities classified into quadrant I (Main Priority) consisting of security and orderliness, comforting facilities in restrooms, temperature control facilities, availability smoking area, and convenient passenger baggage services. Meanwhile, the available facilities on boat included 2 (two) service facilities classified into quadrant I (Main Priority) consisting of boat noise level and seating information on speed boats.Keywords: Performance evaluation, CSI, IPA, Speed Boat, Port StationABSTRAK: Kondisi operator pada Pelabuhan Tengkayu I Kalimantan Utara sering kali terlihat membawa penumpang melebihi kapasitas muat Speed Boat demi mendapatkan keuntungan lebih tanpa memikirkan kenyamanan dan keselamatan penumpang. Hal ini berdampak pada kenyamanan dan keselamatan penumpangpun terabaikan. Metode Customer Satisfaction Index (CSI) adalah bentuk pengukuran yang dipakai untuk menghitung tingkat kepuasan dari keseluruhan atribut pelayanan dengan memperhatikan tingkat harapan yang di hitung. Metode Importance Performance Analysis (IPA) dipakai untuk menganalisis atau membandingkan kualitas layanan yang dirasakan pengguna layanan dengan tingkat kepuasan yang diharapkan. Penelitian yang dilakukan menggunakan metode CSI dapat disimpulkan secara keseluruhan atribut pelayanan yang ada pada pelayan angkutan Speed Boat rute Tarakan Tanjung selor sudah baik. Atribut pelayanan yang ada terminal memiliki angka indeks indeks sebesar 65,72%, Sedangkan pada atribut pelayanan dikapal itu sendiri memiliki angka indeks sebesar 67,60%. Tingkat kepuasan penumpang terhadap fasilitas yang ada di terminal dan kapal pelabuhan Tengkayu I dengan menggunakan metode IPA diklasifikasi menjadi 4 kuadran. Fasilitas yang ada di terminal Terdapat 5 (lima) fasilitas pelayanan yang termasuk dalam kuadran I (Prioritas Utama) yaitu, fasilitas keamanan dan ketertiban, kenyamanan fasilitas di toilet,Â  fasilitas pengatur suhu, tersedianya area merokok, dan kemudahan pelayanan bagasi. Sedangkan fasilitas yang ada di kapal terdapat 2 (dua) fasilitas pelayanan yang termasuk dalam kuadran I (Prioritas Utama) yaitu, tingkat kebisingan di kapal dan informasi untuk mengetahui tempat duduk sesuai tiket.Kata kunci: Evaluasi kinerja, CSI, IPA, Speed Boat, Terminal